Effect of Spirulina platensis Supplementation by Different Concentration in Diet on Red Color Intensity of Kohaku Koi (Cyprinus carpio L.) - N.B.P Utomo; O. Carman; F. Fitriyati (Jurnal Akuakultur Indonesia)
Kohaku koi (Cyprinus carpio) is one of the fancy koi that has a high price.  Red color intensity of kohaku determines its market price.  This study was performed to verify the effect of Spirulina platensis supplementation in diet  with different dosages (1, 3 and 5%) on red color intensity of kohaku koi.  The result of study show that inclusion of Spirulina platensis in the diet increased intensity of koi color.  Feeding with  1% of Spirulina platensis enriched paste diet for 5 weeks resulted in  a brighter red color compared to other treatments and control.   Alteration of red color intensity has not been followed by its patch length.  No effect of Spirulina supplementation on koi growth by weight and length were observed.